Tinjuan Yuridis Pemekaran Wilayah Daerah Provinsi Berkaitan Dengan Wacana Pemekaran Provinsi Nusa Tenggara Timur (NTT) - Ama, Jefrianus Tamo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In principle, the formation of provincial regional expansion, according to the 1945 Constitution of the Unitary State of the Republic of Indonesia in article 18B (1), expressly states that the Unitary State of the Republic of Indonesia consists of provincial districts/cities which have regional autonomy. Therefore, the formation of new provinces is an implementation of the decentralization principle in the 1945 Constitution. Regional expansion is a process of forming new autonomous regions from an existing region. The formation of new regional expansions is based on the principle of decentralization which applies the division of authority to regulate the regional household itself. The discourse on the expansion of East Nusa Tenggara Province is an aspiration from the people, this is just a discourse or issue which was then responded to by several politicians and members of the People's Representative Council of the Republic of Indonesia. Therefore, the expansion of provincial regions is based on Law no. 23 of 2014 concerning regional governments and implementing regulations, Government Regulation of the Republic of Indonesia Number 78 of 2007 concerning Procedures for the Formation, Abolition and Merger of Regions. In this regulation, as the implementer of Law no. 24 of 2014, which includes implementation procedures, mechanisms and procedures for establishing regional areas. In this research, the author uses a normative juridical research approach, and sociological analysis based on existing secondary data, namely from: Books, magazines, journals, newspapers, websites, as a benchmark for this author or authors